Post-exilic conflict as "possible" historical background to Psalm 69:10ab - Groenewald, Alphonso (HTS teologiese studies, 2005)
As is the case with Psalm 8a, Psalm 69:10a, also commences with the emphatic particle kî. 10a and 10b are syndetically bound together by means of the conjunction “and”. What has already been stated in cola 8ab, is repeated and even expressed in clearer terms in these cola (10ab). The supplicant does not believe that he deserves his present distress. Actually, the distress and insult he is enduring come as a direct result of his devotion to God and God’s service. Even his fasting and mourning contribute to his suffering (11a-12b). What becomes increasingly evident is the fact this inner-group conflict is caused by the temple, or rather the debate about the significance of the temple. The question that does indeed arise, is whether it is possible to situate these statements historically. This article will pursue a possible dating for this conflict that can form a possible background against which the reader of this text could interpret the statements contained in these cola (Ps 69:10ab).